VALUES CLARIFICATIONS IN MARITAL RAPE: A NIGERIAN SITUATION - Ola, Tolulope Monisola; Ajayi, Johnson Olusegun (European Scientific Journal, ESJ, 2013)
This paper focuses on the volatile and ignored issue of rape within the context of marriage in Nigeria. It is a topic that is not discussed as a form of domestic and sexual violence against women because of some sociocultural factors like religion, unbalanced gender, norms, early marriage, particularly and power relations. There is a need to look at the issues of marital rape from the lens of Morals and values because of the parlance in which sociologists operate and the need to provide an adequate understanding of human beings within the society. An attempt will be made in this paper to describe marital rape, the cultural contextualization and the basis of the evaluation of human behavior as determined by values.